Ischemic monomelic neuropathy following arteriovenous fistula surgery: a case report - Da Woon Kim; You Hyun Jeon; Miju Bae; Sang Heon Song (Journal of Yeungnam Medical Science)
Ischemic monomelic neuropathy (IMN) is an uncommon complication of arteriovenous fistula (AVF) surgery that presents with pain, motor weakness, and sensory changes without critical ischemia. This report describes a rare case of successful IMN treatment after AVF surgery. A 61-year-old man with diabetic end-stage kidney disease was admitted for left brachiocephalic AVF surgery. Postoperatively, the patient complained of pain, motor weakness, and numbness in the left hand. However, the radial pulse remained palpable, and the overlying skin remained intact. A nerve conduction study above the wrist revealed reduced compound muscle action potential (CMAP) of the left ulnar nerve and no CMAP of the left median nerve. This study also showed the absence of sensory amplitude in both the left median and left ulnar nerves. Therefore, the patient was diagnosed with IMN. Proximalization of the arterial inflow surgery was performed to redistribute blood flow while maintaining the AVF. The patient’s neurological symptoms resolved postoperatively. Various conditions can cause hand pain after AVF surgery; however, IMN has rarely been reported. A multidisciplinary approach is needed to avoid this rare complication in patients presenting with hand pain after AVF surgery.